2021
DOI: 10.1101/2021.10.01.462794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dcp2 C-terminal Cis-Binding Elements Control Selective Targeting of the Decapping Enzyme by Forming Distinct Decapping Complexes

Abstract: A single Dcp1-Dcp2 decapping enzyme targets diverse classes of yeast mRNAs for decapping-dependent 5′ to 3′ decay, but the molecular mechanisms controlling selective mRNA targeting by the enzyme remain elusive. Through extensive genetic analyses we uncover cis-regulatory elements in the Dcp2 C-terminal domain that control selective targeting of the decapping enzyme by forming distinct decapping complexes. Two Upf1-binding motifs target the decapping enzyme to NMD substrates, and a single Edc3-binding motif tar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…In vitro pull-down assays demonstrated that each of these HLMs, except for HLMs 1 and 9, can directly interact with the decapping activator PatL1 (Pat1) ( Charenton et al, 2017 ). In vivo deletions further suggested that HLMs 2–6 (equivalent to HLMs 1-5 in the He et al study) contributed the bulk of PatL1 (Pat1) binding ( He et al, 2021 ). Intriguingly, a strain bearing the deletion of HLMs 2–9 (equivalent to all HLMs in the He et al study) still decays endogenous decapping targets as efficiently as wild-type ( He et al, 2021 ).…”
Section: The Dcp1/2 Complex Is the Main Decapping Holo-enzyme In Euka...mentioning
confidence: 93%
“…In vitro pull-down assays demonstrated that each of these HLMs, except for HLMs 1 and 9, can directly interact with the decapping activator PatL1 (Pat1) ( Charenton et al, 2017 ). In vivo deletions further suggested that HLMs 2–6 (equivalent to HLMs 1-5 in the He et al study) contributed the bulk of PatL1 (Pat1) binding ( He et al, 2021 ). Intriguingly, a strain bearing the deletion of HLMs 2–9 (equivalent to all HLMs in the He et al study) still decays endogenous decapping targets as efficiently as wild-type ( He et al, 2021 ).…”
Section: The Dcp1/2 Complex Is the Main Decapping Holo-enzyme In Euka...mentioning
confidence: 93%
“…Strains containing complete gene deletions of UPF1, UPF2, and UPF3 (HFY871, HFY115, HFY861, HFY467) were described previously 25,45 . HFY2996 and HFY3039 were described previously 28 . YRG5205 was generated from HFY3039 with a complete gene deletion of UPF1 as in HFY871.…”
Section: Methodsmentioning
confidence: 99%
“…Dcp2, the catalytic component of the decapping enzyme, is also found on translating ribosomes 26 , and the co-translational recruitment of Dcp2 to NMD substrates is likely to occur via two highly similar Upf1-binding sites on Dcp2 27 . To address whether ribosome-associated Upf1 plays a role in recruitment of Dcp2, centromeric UPF1-FLAG was expressed in strains containing genomic HA-tagged DCP2 or the HA-dcp2-U1D-U2D allele in which the two Upf1 binding sites have been deleted 28 . Sucrose gradient fractionation and western blotting demonstrated that deletion of the Upf1-binding sites on Dcp2 slightly shifted Dcp2 to lighter fractions (Figure 2b).…”
Section: Distinct States Of Polysome Association By Upf1 and Its Binding Partnersmentioning
confidence: 99%
See 2 more Smart Citations